Outdoor play activities in optimizing motor skills in children: a systematic review - Alfroki Martha; Heru Andika; Anton Komaini; Yanuar Kiram; Asep Sujana Wahyuri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Motor skills are the foundation for early childhood development, playing an active role in learning readiness, health, and behavior. However, changes in lifestyle have made children increasingly dependent on digital technology, leading to reduced outdoor play time. This situation impacts children's opportunities to develop coordination, muscle strength, and body balance. This study aims to review, analyze, and identify the extent to which outdoor play activities contribute to early childhood motor skills. A systematic review method was used with PRISMA guidelines. Eight articles met the inclusion criteria from the Scopus, PubMed, and ScienceDirect search platforms. The review findings conveyed that outdoor play activities improve children's balance, body coordination, and motor skills. This positive impact is supported by factors such as activity duration, play environment, and parents. This study shows that outdoor play activities are an effective experience-based educational strategy to promote motor development and the overall well-being of early childhood children.